Baseline description of the Benthic Biotopes for two Long-Term Ecological Research (LTER) stations in Algoa Bay, Agulhas ecoregion, South Africa - Parker-Nance, Shirley (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
Shallow coastal marine ecosystems provide important resources to society but are increasingly under threat from anthropogenic impacts. These systems form an interface between land and sea, providing valuable resources. Global environmental change, overexploitation, habitat transformation, pollution and policies aimed at short-term socio-economic gains are driving the loss of natural resources, productivity and biodiversity. Consequently, a comprehensive and holistic understanding of the current and future states of marine ecosystems is essential. This requires insight into the processes involved in maintaining genetic, species, habitat, community and biotope diversity at an ecosystem level. An understanding of ecosystem processes and the ability to detect changes in biodiversity, biotopes, seascape composition and ecosystem functioning require observation made over time and space. In response to this need, Long-Term Ecological Research (LTER) programmes such as those established by the South African Environmental Observation Network (SAEON) supported by the Department of Science and Innovation's (DSI) Shallow Marine and Coastal Research Infrastructure (SMCRI) collect long"“term observational data from different environments and systems. This study aimed to evaluate data collected as part of the developmental phase of a newly established benthic research platform. The datasets constructed are used to develop a baseline description of the benthic biotopes of two study areas within Algoa Bay. It aimed to gain insight into the feasibility of the methods used and the value of the data and derived essential biological variables (EVB). Assessing the sustainability of the programme over time was done through a practical evaluation of the methodology to be used and the technical feasibility of data collection and analysis. It furthermore aimed to assess the data usefulness in describing biodiversity at various scales and its sensitivity in reporting change. This pilot study provides valuable insight into data collection methodologies and introduces new sampling platforms. The baseline dataset consisted of data collected during the first 18 months of the SAEON Benthic Ecosystem Long-Term Ecological Research (BELTER) platform in Algoa Bay, Agulhas ecoregion, Western Indian Ocean, South Africa. This comprised of the collection of images for 150 m2 of the researched benthic seascape and 306 stereo video data streams. The 77 760 point dataset allowed the identification of 12 substrate types, 7 biotopes, 44 sub-biotope units, 377 sessile and sedentary benthic species and 51 ichthyofauna species. The described habitat and benthic communities and the defined benthic biotopes allowed for the assessment of biotope heterogeneity and the construction of a provisional distribution map for the broader biotopes. This work includes a study into the infra- and supra-benthic ichthyofauna associated with the defined biotopes and investigates the role habitat and benthic communities play in the distribution of these fish 3 assemblages. Lastly, it assesses the value of morphological traits and diversity indices for describing and comparing abiotic and biotic components of observed systems within the shallow coastal marine seascape. This study shows that species composition differs significantly between biotopes with habitat type playing a key role in the composition of the benthos. Substrate type, consolidated or unconsolidated, depth and the composition of the soft sediment is the most important determining factors. The White Sands Reef station has a higher species diversity than the St Croix Island Complex station with a higher percentage cover associated with the hard substrate. The dissimilarity between biotopes and communities are generally high although similarity within the biotopes or communities was found to be relatively low. This was considered indicative of high heterogeneity within the biotopes and a patch or mosaic-like distribution of communities within the broader biotope. A fine-scale a posteriori analysis of the data collected confirmed the high heterogeneous nature of both habitat and communities within the broader biotope. The description of the abiotic and biotic variables resulted in the identification of a diverse suite of biotope subunits. The character of the biotope hinges not only on the composition of the substrate and biota present but the contribution of smaller distinct biotopes subunits, their distribution and representation within broader biotopes and the degree these are shared with other broader biotopes. The distribution of these biotope units at different scales is believed to be important in understanding inherent diversity, niche partitioning and connectivity within a highly heterogeneous seascape. Ichthyofauna associated with the broader biotopes were indicative of the substrate type. Low profile reef systems with interspaced sandy stretches supported both reef fish and those typically associated with sandy substrates. Benthic biotopes associated characteristically with higher profile reef systems and less sand or soft sediment were mainly utilized by reef-associated fish species. Substrate type, depth and seasonality were found to be important factors in the observed composition and distribution of ichthyofauna over the seascape. Although fish species were found to have a wide distribution and made use of multiple biotopes the average abundance of the species within the observed assemblages differed. Analysis of ichthyofauna species composition indicated that observed fish assemblages were homogeneous within five of the seven biotopes. Broader biotopes that were found to be significantly different between sample locations are characterised by a diverse complement of biotope subunits and are highly heterogeneous. Traits and diversity indices are important tools for assessing and comparing different systems within the seascape, both spatially and temporally. The classification of the biota into broader phylogenetic groups indicated a significant difference between biotopes. This is especially useful when detailed 4 analysis or species identification is not possible or the skill set is not available. Morphological traits included in this study informed on the physical structure of the communities present and in combination with substrate type provided insight into the three-dimensional structure of the biotope. Species diversity, abundance, density estimates and the Shannon-Weiner diversity index were found to be the most useful diversity indices characterising and comparing biotopes. This was less so for ichthyofauna. Significant differences in the number of species observed were evident only between consolidated and unconsolidated dominated substrates. Although there was no significant difference in the number of individuals observed, both the Shannon-Weiner and Simpson Diversity indices were able to highlight differences in the fish assemblages observed for the different biotopes. The data collected, although permitting a comprehensive baseline assessment of the benthic environment for two research stations within the SAEON Algoa Bay LTER Sentinel Site, is temporally limited. The ichthyofauna dataset used was small and it is understood that the addition of length-frequency analysis of observed ichthyofauna will benefit our understanding of the biotope use by infra- and supra-benthic fish species over their life history within the larger seascape. Seasonal differences were evident and it is expected that datasets spanning several years, including LTER stations within different marine ecosystems types, will provide valuable insights on system dynamics in the short and long term both spatially and temporally. This study is the first attempt to evaluate the methodology developed and data collected in the South African Environmental Observation Network's, Elwandle Coastal Node as part of the Shallow Marine and Coastal Research Infrastructure Benthic Ecosystem Long-Term Ecological Research (BELTER) platform. Newly designed and developed sample equipment and a sampling regime allowed for the collection of data on a long-term basis. The study was successful in the description of the biotope and biotope subunits for two research stations in Algoa Bay. It permitted the construction of comprehensive species lists for both benthic sessile and sedentary biota and the associated ichthyofauna. The subset of data used was successful in reporting on both spatial and temporal change. This work demonstrates that in the absence of detailed species identifications, traits may be used to describe habitat and community structure and report on abiotic and biotic biotope characteristics. This study furthermore allowed for the comparison of a comprehensive suite of diversity indices highlighting indices that may be especially useful in routine BELTER reporting.,Thesis (PhD) -- Faculty of Science, Ichthyology and Fisheries Science, 2021
Keywords: Benthic ecology -- South Africa Algoa Bay; Long-Term Ecological Research Program; Marine invertebrates -- South Africa Algoa Bay; Reef ecology -- South Africa Algoa Bay; Coastal zone management -- South Africa Algoa Bay; Reef fishes -- South Africa Algoa Bay; Ecological mapping -- South Africa Algoa Bay